Regulation of potassium transport in plants under hostile conditions: implications for abiotic and biotic stress tolerance - Shabala, Sergey; Pottosin, Igor (Physiologia plantarum, 2014)
Intracellular potassium homeostasis is a prerequisite for the optimal operation of plant metabolic machinery and plant's overall performance. It is controlled by K⁺ uptake, efflux and intracellular and long‐distance relocation, mediated by a large number of K⁺‐selective and non‐selective channels and transporters located at both plasma and vacuolar membranes. All abiotic and biotic stresses result in a significant disturbance to intracellular potassium homeostasis. In this work, we discuss molecular mechanisms and messengers mediating potassium transport and homeostasis focusing on four major environmental stresses: salinity, drought, flooding and biotic factors. We argue that cytosolic K⁺ content may be considered as one of the ‘master switches’ enabling plant transition from the normal metabolism to ‘hibernated state’ during first hours after the stress exposure and then to a recovery phase. We show that all these stresses trigger substantial disturbance to K⁺ homeostasis and provoke a feedback control on K⁺ channels and transporters expression and post‐translational regulation of their activity, optimizing K⁺ absorption and usage, and, at the extreme end, assisting the programmed cell death. We discuss specific modes of regulation of the activity of K⁺ channels and transporters by membrane voltage, intracellular Ca²⁺, reactive oxygen species, polyamines, phytohormones and gasotransmitters, and link this regulation with plant‐adaptive responses to hostile environments.